Antecdents and conequences of consumer internet of things security self efficiency - Behardien, Raeesa (Department of Information Systems, 2024)
The Internet of Things (IoT) is defined as the next great era of communication and comes with the promise of massive transformations to society and the way the internet works. The growth and demand of IoT devices has led to the increased production of unsecure connected devices that have managed to enter the physical world with many distinct applications. Consumer IoT devices are increasingly available and adopted in all its various forms. Consumer IoT devices can connect to any environment using an internet connection, so it becomes important to secure them against vulnerabilities and security threats. Users of Consumer IoT may be aware of and understand the information security threats they face; however, their self-efficacy affects their ability to protect themselves. The consumers self-efficacy represents the ability to carry out responsive behaviours and the belief that the applied responsive behaviour will have the desired impact. It has been determined to affect their ability to secure Consumer IoT devices and their ability to appropriately respond to the various threats. This research study contributes to the information security area of knowledge by means of a quantitative study with 230 South African respondents. Here, the focus is on the antecedents and consequences of consumer IoT security self-efficacy while evaluating the constructs: IoT Security Behavioural Practices, Behavioural Intention, IoT Security Technology Practices, IoT Security Self-Efficacy, IoT Device Knowledge, IoT Device Experience, IoT Security Breach Incidents, and Consumer IoT General Controllability. The findings from this study show that the consumer IoT device knowledge and consumer IoT general controllability of the user are the antecedents of consumer IoT security self-efficacy. The consequences of consumer IoT security self-efficacy are IoT security technology practices, behavioural intention and IoT security behavioural practices. Similarly, the findings show that there is a positive relationship between the consumers behavioural intention and the IoT security behavioural practices that they carry out.